Stellenwert des kreativen Schreibens im DaF-Unterricht aus der Sicht der polnischen Deutschlehrenden - Przymusińska, Aleksandra (Glottodidactica, 2024)
The article aims to present selected approaches and organisational methods for (creative) writing skills in German as a foreign language (GFL) at the secondary and tertiary educational level from the teacher’s perspective. The text production processes described in this article refer both to theory in the field of (creative) text writing methods and the analysis of the results of two questionnaires conducted among Polish teachers of German as a foreign language. The analysis of current language writing didactics in Polish schools indicates discrepancies between the methodological abilities of the teachers and the actual implementation of the methods in the process of writing in German. Unfortunately, the teacher’s attitude towards using creative writing methods as innovative solutions to support writing competence in teaching in the field of German as a foreign language is not reflected in their levels of theoretical knowledge. Such an approach, being processoriented and student-oriented, must not focus solely on the outcome, namely the written German text, but on the role of its author and the writing process. The article concludes with suggestions for enhancing the significance of (creative) writing didactics in German classes in Polish schools.